The Pathophysiological Mechanisms and the Quest for Biomarkers in Psoriasis, a Stress-Related Skin Disease. (28th January 2018) - Tampa, Mircea; Sarbu, Maria-Isabela; Mitran, Madalina-Irina; Mitran, Cristina-Iulia; Matei, Clara; Georgescu, Simona-Roxana
Abstract : Psoriasis is a physically, emotionally, and socially invalidating multifactorial disorder, with a significant impact on the patients' quality of life. Stress is one of the leading triggers for psoriasis and has been associated with disease onset and subsequent flare-ups, while the flare-ups by themselves often lead to psychological discomfort. The treatment of psoriasis is individualized, depending on the patients' measurable severity of illness, as well as the impact the skin condition has on patients' quality of life, as assessed by standardized questionnaires. The clinical scales used nowadays for measuring the severity of psoriasis are characterized by low reproducibility and high variability between examiners. Hence, there is a real need to identify objectively measurable biomarkers to standardize the assessment of the severity of psoriasis. We aim to review the pathophysiological mechanisms involved in psoriasis, focusing on the most critical advances in psoriasis biomarker discovery, pointing out those biomarkers which have also been studied in other stress-related conditions, thus emphasizing the relationship between psoriasis and stress.